A Preventive and Control Strategy for COVID-19 Infection: An Experience From a Third-Tier Chinese City - Shushan Fan; Min Wu; Shengjun Ma; Shouguo Zhao (Frontiers Media S.A., 2020)
COVID-19 is a rapidly spreading infectious disease that has led to a global pandemic. This study describes a novel strategy for preventing and controlling COVID-19 infection in the third-tier city of Liaocheng, China. The prevention and control measurements included city-wide orders to close workspaces, sanitize essential workspaces, quarantine individuals with a travel history to an epidemic area, and issue emergency medical responses to quarantine and treat COVID-19 patients using all necessary technologies, personnel, and resources. As a result, there were only 38 diagnosed COVID-19 cases in Liaocheng since the pandemic began in China in late 2019, including in the metropolitan area and six suburban counties, accounting for more than 6.39 millions residents living in a 8,715 km2 area. There was no COVID-19-related fatality and no healthcare professional inter-transmission as of June 25, 2020. The strategies of this third-tier Chinese city provide useful insights into approaches to prevent and control COVID-19 spread in other Chinese cities and countries.